Abusive endings : separation and divorce violence against women - DeKeseredy, Walter S., 1959-; Dragiewicz, Molly; Schwartz, Martin D. (Oakland, California : University of California Press, 2017)
"Abusive Endings offers a thorough analysis of the social-science literature on one of the most significant threats to women's health and well-being today--abuse at the hands of their partners. The authors provide a moving description of why and how men abuse women in myriad ways during and after a separation or divorce. The material is punctuated with the stories and voices of both perpetrators and survivors of abuse, as told to the authors over many years of fieldwork. Written in a highly readable fashion, this book will be a useful resource for researchers, practitioners, activists, and policy makers"--Provided by publisher.
Conceptualizing separation/divorce violence against women -- The extent and distribution of separation/divorce assault -- New technologies and separation/divorce violence against women -- Explaining separation/divorce violence against women -- Children as collateral victims of separation/divorce woman abuse -- What is to be done about separation/divorce violence against women?
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072
Keywords: Family violence -- United States; Family violence; United States; POLITICAL SCIENCE / Public Policy / Social Security; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; SOCIAL SCIENCE / Criminology; Electronic books